Mapping Fusarium solani and Aphanomyces euteiches Root Rot Resistance and Root Architecture Quantitative Trait Loci in Common Bean. Issue 5 (1st September 2015) - Hagerty, C. H.; Cuesta‐Marcos, A.; Cregan, P. B.; Song, Q.; McClean, P.; Noffsinger, S.; Myers, J. R.
ABSTRACT: Root rot diseases of bean ( Phaseolus vulgaris L.) are a constraint to dry and snap bean production. We developed the RR138 RI mapping population from the cross of OSU5446, a susceptible line that meets current snap bean processing industry standards, and RR6950, a root rot resistant dry bean with small brown seeds. We evaluated the RR138 RI population beginning in the F6 generation for resistance to Fusarium solani f. sp. phaseoli (Burk.) root rot in Oregon and Aphanomyces euteiches (Drechsler) root rot in Wisconsin. The population was evaluated for a set of root architecture traits at the Oregon location. Fusarium solani root rot resistance was evaluated in three seasons, whereas A. euteiches resistance was evaluated in two seasons. For each disease, RR6950 was resistant and OSU 5446 was susceptible. The recombinant inbred (RI) population was normally distributed for reaction to both diseases. We assembled a high‐density linkage map using 1689 single‐nucleotide polymorphisms (SNPs) from an Illumina 6000‐SNP BARCbean6K_3 Beadchip. The map spanned 1196 cM over 11 linkage groups at a density of one SNP per 1.4 cM. Three quantitative trait loci (QTL) associated with A. euteiches were identified, each accounting for 5 to 15% of the total genetic variation, and two QTL associated with F. solani resistance accounted for 9 and 22% of the total genetic variation. A QTL for taproot diameter (TD) and one QTL for basal root angle were identified. The QTL for resistance to the two diseases mapped to different genome locations indicating a different genetic control.